Concrete suitable for internal pouring of steel lattice column and construction method thereof
By using concrete with modified gangue and composite admixtures in the steel lattice column, the problems of conduit shaking and hollowing are solved, and efficient pouring and high-quality concrete pouring are achieved.
Patent Information
- Application Number
- CN202410147832.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-02-02
AI Technical Summary
When concrete is poured into the steel lattice column, the conduit is prone to shaking, shifting, and falling in the traditional method, which affects the quality of concrete pouring, and causes hollowing due to difficulties in water analysis and insufficient vibration.
Concrete with components such as modified coal gangue and composite admixture is used to form a pore structure through the calcination of modified coal gangue, and the flowability, strength and self-compensation performance of the concrete are improved through the sustained release expansion effect of the composite admixture.
It realizes efficient pouring of concrete in steel lattice columns, avoids hollowing, improves the flowability and strength of concrete, and ensures high-quality pouring of column core concrete.
Smart Images

Figure QLYQS_1 
Figure BDA0004694567970000061 
Figure BDA0004694567970000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building concrete and relates to concrete suitable for internal pouring of a steel lattice column and a construction method thereof. Background Art
[0002] Steel tube concrete columns have the characteristics of high bearing capacity, good ductility, and superior seismic performance, and have been widely used in large exhibition projects and high-rise structural buildings. Due to the complex internal structure of steel tube columns and the large number of horizontal and vertical internal partitions, the traditional practice is to use the conduit method to cast them. A long conduit is inserted from the top of the steel column into the steel column, and the concrete falls freely from the conduit to the bottom of the steel column, using the concrete's own kinetic energy to achieve the purpose of self-compacting and vibration-free. However, during the construction process, due to the lateral pressure of the upper concrete pouring and the gravity of the long conduit itself, the conduit is prone to shaking, shifting, and falling during the concrete pouring, which brings great inconvenience to the construction and seriously affects the quality of the column core concrete pouring. In addition, due to the airtightness of the steel tube, the water in the concrete cannot be precipitated, and the vibrating rod vibrates in the narrow tube, the coarse aggregate sinks relatively, and the mortar floats, so that the excess water in the concrete floats to the top of the tube, forming a mortar layer and a water seepage layer on the top of the tube. The shrinkage of concrete during the hardening process can also easily lead to loose bonding between the tube wall and the concrete, resulting in hollowing.
[0003] The measures to reduce concrete shrinkage are generally to select high-quality concrete raw materials, or reduce the water-cement ratio to prevent the concrete from shrinking during the drying process due to the excessive water-cement ratio, or to use micro-expansive concrete, because micro-expansive concrete will expand slightly during the curing process, thereby reducing the concrete curing shrinkage, and finally to do a good job of curing concrete. However, reducing the water-cement ratio will affect the fluidity of concrete to a certain extent, making it difficult to construct, and it is easy to have problems such as voids and cracks when pouring concrete. Summary of the invention
[0004] The main purpose of the present invention is to provide a concrete suitable for internal pouring of steel lattice columns, the concrete has the characteristics of good fluidity, small shrinkage and high strength, and the column piles poured with the concrete have high bearing capacity and excellent performance.
[0005] The present invention adopts the following technical solutions to achieve the above purpose:
[0006] A concrete suitable for internal pouring of a steel lattice column, comprising the following components in parts by weight:
[0007] 300-330 parts of Portland cement
[0008] Fly ash 100-120 parts
[0009] Sand 730-750
[0010] Stone 850-900
[0011] 30-50 parts of modified coal gangue
[0012] Composite admixture 12-20 parts
[0013] Air entraining agent 0.15-0.2 parts
[0014] 180-200 parts of water;
[0015] The composite admixture includes 3-4 parts of sodium polyacrylate, 2-3 parts of micro-powder silica gel, 1-2 parts of aluminum sulfate, 1-3 parts of sodium silicate and 5-8 parts of sodium alginate.
[0016] Furthermore, the air entraining agent includes 0.09-0.1 parts of sodium dodecyl sulfate, 0.04-0.05 parts of triterpenoid saponin, and 0.02-0.05 parts of polyvinyl pyrrolidone.
[0017] The present invention provides a method for preparing the modified coal gangue, which specifically comprises the following steps:
[0018] (1) crushing the coal gangue into 50-80 mesh, adding it into a phosphoric acid solution with a concentration of 8-10%, soaking it for 20-24 hours, filtering it, and drying it to obtain acid-leached coal gangue powder;
[0019] (2) mixing the acid-leached coal gangue powder and the shell powder uniformly, calcining at 800-850° C. for 1-1.5 hours under nitrogen protection, and naturally cooling to 60-80° C. after calcination to obtain a calcined mixed powder;
[0020] (3) Add polyvinyl alcohol to the calcined mixed powder under vacuum at 60-80° C., stir for 1-1.5 hours, then add dimethyl silicone oil and stir for 1-1.5 hours, and then ball-mill to 120-150 mesh to obtain modified coal gangue.
[0021] Furthermore, in step (2) of the above preparation method, the amount of shell powder added is 15-20% of the weight of the coal gangue; in step (3), the amount of polyvinyl alcohol added is 20-25% of the weight of the coal gangue, and the amount of dimethyl silicone oil added is 30-35% of the weight of the coal gangue.
[0022] The present invention provides a construction method for the above concrete, comprising the following steps:
[0023] S1, mixing 1 / 3 of the total weight of silicate cement and modified coal gangue evenly under mechanical stirring to obtain dry material;
[0024] S2, adding sodium polyacrylate, micro-powder silica gel, aluminum sulfate and sodium silicate to molten sodium alginate, mixing evenly, and drying to obtain a composite admixture;
[0025] S3, mixing the remaining Portland cement, fly ash, sand, gravel, air entraining agent and water evenly under mechanical stirring, then adding the composite admixture, continuing to stir and mix evenly to obtain slurry;
[0026] S4, 1-1.5 hours before pouring, add the dry material obtained in S1 to the slurry obtained in S3, mix well, and obtain concrete.
[0027] The present invention has the following beneficial effects:
[0028] 1. In the present invention, the coal gangue is calcined and modified. Acid leaching is used before calcination to effectively remove metal elements in the coal gangue, and also to activate the metal elements and penetrate into the interior of the coal gangue. Under high-temperature calcination, a rich pore structure is generated inside the coal gangue. At the same time, shell powder is added during the calcination process. The main component of the shell powder is calcium carbonate. Under high-temperature calcination, it decomposes to produce CO2. CO2 can enter the pores of the coal gangue for etching, so that the pore structure inside the coal gangue is more developed; after high-temperature calcination, polyvinyl alcohol and dimethyl silicone oil are used to seal the calcined coal gangue, so that the pore structure of the coal gangue is more stable. The modified coal gangue prepared in this way has enhanced adsorption performance. When used for concrete preparation, it can effectively improve its water retention performance, maintain the early fluidity of the concrete mixture, and facilitate pumping.
[0029] 2. In the present invention, sodium polyacrylate, micropowder silica gel, aluminum sulfate and sodium silicate are added to sodium alginate in a molten state to prepare an expansion agent with a sustained release effect. When used in concrete preparation, the expansion agent can be slowly released and expanded, and has good expansion performance. After effective expansion, no inverted shrinkage occurs, and the volume shrinkage of the concrete itself during the hardening process and the capillary shrinkage caused by the hydration heat are effectively filled, so as to achieve the effect of maintaining the volume stability of the concrete, and improve the density of the concrete and the strength of the concrete; at the same time, the hollowing phenomenon caused by the loose bonding between the tube wall and the concrete due to the shrinkage of the concrete during the hardening process is avoided.
[0030] 3. During the construction process of the concrete of the present invention, coal gangue is mixed with part of cement to form dry powder, which is then added to the concrete mortar 1-1.5 hours before pouring. The subsequent addition of part of cement and coal gangue can effectively improve the fluidity of the concrete mortar and facilitate its pouring. After the addition of coal gangue, the components in the composite additive are also slowly released, and synergistically act with the coal gangue to form a gel network, thereby avoiding the sinking of crushed aggregates and making them evenly distributed, which can effectively avoid the bleeding of concrete.
[0031] In summary, the concrete provided by the present invention has the following advantages:
[0032] Good fluidity: It can be used for construction of structures with dense steel bars, narrow space and complex shapes without vibration or slight vibration, which is convenient for construction;
[0033] Superior performance: The components work together to increase the overall structural density and impermeability, with high strength and no water seepage;
[0034] Strong self-compensation performance: The synergistic effect between coal gangue and composite admixtures enables the micro-expansion during the concrete preparation process to effectively control the volume shrinkage of concrete, achieve a better micro-expansion state to compensate for shrinkage, reduce its shrinkage value, and maintain volume stability. DETAILED DESCRIPTION
[0035] The present invention is further explained below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent modifications to the present invention by those skilled in the art all fall within the scope of protection of the claims of this application.
[0036] Example 1
[0037] Preparation of modified coal gangue:
[0038] (1) crushing 100 kg of coal gangue into 80 meshes, adding it into a phosphoric acid solution with a concentration of 8%, soaking it for 20 hours, filtering it, and drying it to obtain acid-leached coal gangue powder;
[0039] (2) mixing the acid-leached coal gangue powder and 20 kg of shell powder evenly, calcining at 850° C. for 1 hour under nitrogen protection, and naturally cooling to 60° C. after calcination to obtain a calcined mixed powder;
[0040] (3) Under vacuum at 60°C, 25 kg of polyvinyl alcohol was added to the calcined mixed powder, stirred for 1.5 hours, and then 30 kg of dimethyl silicone oil was added and stirred for 1 hour. The mixture was then ball-milled to 120 mesh to obtain modified coal gangue.
[0041] Concrete construction:
[0042] S1, 100 kg of Portland cement and 30 kg of modified coal gangue are mixed evenly under mechanical stirring to obtain dry material;
[0043] S2, add 3kg of sodium polyacrylate, 2kg of silica gel powder, 1kg of aluminum sulfate, and 1kg of sodium silicate to 5kg of molten sodium alginate, mix well, and dry to obtain 12kg of composite admixture;
[0044] S3, 200kg of Portland cement, 120kg of fly ash, 730kg of sand, 900kg of gravel, 0.2kg of air entraining agent (0.1kg of sodium lauryl sulfate, 0.05kg of triterpenoid saponin, 0.05kg of polyvinyl pyrrolidone), and 180kg of water are mixed uniformly under mechanical stirring, and then the composite admixture is added, and stirring is continued to mix uniformly to obtain a slurry;
[0045] S4, 1-1.5 hours before pouring, add the dry material obtained in S1 to the slurry obtained in S3, mix well, and obtain concrete.
[0046] Example 2
[0047] Preparation of modified coal gangue:
[0048] (1) crushing 100 kg of coal gangue into 50 meshes, adding it into a 10% phosphoric acid solution, soaking it for 24 hours, filtering it, and drying it to obtain acid-leached coal gangue powder;
[0049] (2) mixing the acid-leached coal gangue powder and 15 kg of shell powder evenly, calcining at 800° C. for 1.5 hours under nitrogen protection, and naturally cooling to 80° C. after calcination to obtain a calcined mixed powder;
[0050] (3) Under vacuum at 80°C, 20 kg of polyvinyl alcohol was added to the calcined mixed powder, stirred for 1 hour, and then 35 kg of dimethyl silicone oil was added and stirred for 1.5 hours. The mixture was then ball-milled to 150 mesh to obtain modified coal gangue.
[0051] Concrete construction:
[0052] S1, 110 kg of silicate cement and 50 kg of modified coal gangue are mixed evenly under mechanical stirring to obtain dry material;
[0053] S2, add 4kg of sodium polyacrylate, 3kg of micro-powder silica gel, 2kg of aluminum sulfate, and 3kg of sodium silicate to 8kg of molten sodium alginate, mix well, and dry to obtain 20kg of composite admixture;
[0054] S3, 220kg of Portland cement, 100kg of fly ash, 750kg of sand, 850kg of gravel, 0.15kg of air entraining agent (0.09kg of sodium lauryl sulfate, 0.04kg of triterpenoid saponin, 0.02kg of polyvinyl pyrrolidone), and 200kg of water are mixed uniformly under mechanical stirring, and then the composite admixture is added, and stirring is continued to mix uniformly to obtain a slurry;
[0055] S4, 1-1.5 hours before pouring, add the dry material obtained in S1 to the slurry obtained in S3, mix well, and obtain concrete.
[0056] Example 3
[0057] Preparation of modified coal gangue:
[0058] (1) crushing 100 kg of coal gangue into 70 meshes, adding it into a 9% phosphoric acid solution, soaking it for 22 hours, filtering it, and drying it to obtain acid-leached coal gangue powder;
[0059] (2) mixing the acid-leached coal gangue powder and 17 kg of shell powder evenly, calcining at 850° C. for 1 hour under nitrogen protection, and cooling naturally to 70° C. after calcination to obtain a calcined mixed powder;
[0060] (3) Under vacuum at 70°C, 22 kg of polyvinyl alcohol was added to the calcined mixed powder, stirred for 1 hour, and then 33 kg of dimethyl silicone oil was added and stirred for 1.5 hours. The mixture was then ball-milled to 130 mesh to obtain modified coal gangue.
[0061] Concrete construction:
[0062] S1, 110 kg of silicate cement and 40 kg of modified coal gangue are mixed evenly under mechanical stirring to obtain dry material;
[0063] S2, add 3kg of sodium polyacrylate, 2kg of micro-powder silica gel, 1kg of aluminum sulfate, and 2kg of sodium silicate to 8kg of molten sodium alginate, mix well, and dry to obtain 16kg of composite admixture;
[0064] S3, 220kg of Portland cement, 110kg of fly ash, 730kg of sand, 880kg of gravel, 0.17kg of air entraining agent (0.1kg of sodium lauryl sulfate, 0.04kg of triterpenoid saponin, 0.03kg of polyvinyl pyrrolidone), and 190kg of water are mixed uniformly under mechanical stirring, and then the composite admixture is added, and stirring is continued to mix uniformly to obtain a slurry;
[0065] S4, 1.5 hours before pouring, add the dry material obtained in S1 to the slurry obtained in S3, mix well, and obtain concrete.
[0066] Comparative Example 1
[0067] Preparation of modified coal gangue:
[0068] (1) crushing 100 kg of coal gangue into 70 meshes, adding it into a 9% phosphoric acid solution, soaking it for 22 hours, filtering it, and drying it to obtain acid-leached coal gangue powder;
[0069] (2) calcining the acid-leached coal gangue powder at 850° C. for 1 hour under nitrogen protection, and naturally cooling to 70° C. after calcination to obtain a calcined mixed powder;
[0070] (3) Under vacuum at 70° C., 33 kg of dimethyl silicone oil was added to the calcined mixed powder and stirred for 1.5 hours, and then ball-milled to 130 mesh to obtain modified coal gangue.
[0071] Concrete construction:
[0072] S1, 110 kg of silicate cement and 40 kg of modified coal gangue are mixed evenly under mechanical stirring to obtain dry material;
[0073] S2, 220kg of Portland cement, 110kg of fly ash, 730kg of sand, 880kg of gravel, 0.17kg of air entraining agent (0.1kg of sodium lauryl sulfate, 0.04kg of triterpenoid saponin, 0.03kg of polyvinyl pyrrolidone), and 190kg of water are mixed uniformly under mechanical stirring, and then a composite admixture (3kg of sodium polyacrylate, 2kg of micropowder silica gel, 1kg of aluminum sulfate, 2kg of sodium silicate, and 8kg of sodium alginate) is added, and stirring is continued to mix uniformly to obtain a slurry;
[0074] S3: 1.5 hours before pouring, add the dry material obtained in S1 to the slurry obtained in S3, mix well, and obtain concrete.
[0075] Comparative Example 2
[0076] Preparation of modified coal gangue:
[0077] (1) crushing 100 kg of coal gangue into 70 meshes, adding it into a 9% phosphoric acid solution, soaking it for 22 hours, filtering it, and drying it to obtain acid-leached coal gangue powder;
[0078] (2) The acid-leached coal gangue powder was calcined at 850° C. for 1 hour under nitrogen protection, and then naturally cooled to 70° C. after calcination to obtain modified coal gangue.
[0079] Concrete construction:
[0080] S1, 110 kg of silicate cement and 40 kg of modified coal gangue are mixed evenly under mechanical stirring to obtain dry material;
[0081] S2, adding 3kg of sodium polyacrylate and 2kg of sodium silicate to 8kg of molten sodium alginate, mixing evenly, and drying to obtain 16kg of composite admixture;
[0082] S3, 220kg of Portland cement, 110kg of fly ash, 730kg of sand, 880kg of gravel, 0.17kg of air entraining agent (0.1kg of sodium lauryl sulfate, 0.04kg of triterpenoid saponin, 0.03kg of polyvinyl pyrrolidone), and 190kg of water are mixed uniformly under mechanical stirring, and then the composite admixture is added, and stirring is continued to mix uniformly to obtain a slurry;
[0083] S4, 1.5 hours before pouring, add the dry material obtained in S1 to the slurry obtained in S3, mix well, and obtain concrete.
[0084] Comparative Example 3
[0085] S1, add 3kg of sodium polyacrylate, 2kg of micro-powder silica gel, 1kg of aluminum sulfate, and 2kg of sodium silicate to 8kg of molten sodium alginate, mix well, and dry to obtain 16kg of composite admixture;
[0086] S2, 330kg of Portland cement, 110kg of fly ash, 730kg of sand, 880kg of gravel, 0.17kg of air entraining agent (0.1kg of sodium lauryl sulfate, 0.04kg of triterpenoid saponin, 0.03kg of polyvinyl pyrrolidone), 40kg of coal gangue and 190kg of water are mixed evenly under mechanical stirring, and then the composite admixture is added, and stirring is continued. Mix evenly to obtain concrete.
[0087] Concrete performance testing
[0088] 1. Referring to GB / T 50080 "Standard for Test Methods for Properties of Ordinary Concrete Mixtures", the concrete samples prepared by the above Examples 1-3 and Comparative Examples 1-3 were tested for fluidity. The results are shown in Table 2.
[0089] Table 1 Concrete sample fluidity test results
[0090]
[0091] From the results in Table 1, it can be seen that the concrete samples prepared by the present invention have good initial fluidity, and within 30 minutes, they all have good fluidity, and the time to pass through the V-funnel is short, and the effect is better than the concrete samples obtained in the comparative example.
[0092] 2. The concrete prepared by the above-mentioned Examples 1-3 and Comparative Examples 1-3 was poured and cured, and the shrinkage and strength performance of the obtained concrete products were tested. The results are shown in Table 2.
[0093] Table 2 Test results of concrete products
[0094]
[0095] From the results in Table 1, it can be seen that the drying shrinkage of the concrete prepared by the present invention is significantly lower than that of the concrete obtained in the comparative example, and its compressive and flexural strengths are significantly higher than those of the concrete obtained in the comparative example. It can be seen that the performance of the concrete prepared by the present invention is superior.
Claims
1. A concrete suitable for pouring inside a steel lattice column, characterized in that: In parts by weight, it contains the following components: The composite admixture includes 3-4 parts of sodium polyacrylate, 2-3 parts of micro-powder silica gel, 1-2 parts of aluminum sulfate, 1-3 parts of sodium silicate, and 5-8 parts of sodium alginate; The air entraining agent comprises 0.09-0.1 parts of sodium lauryl sulfate, 0.04-0.05 parts of triterpenoid saponin, and 0.02-0.05 parts of polyvinyl pyrrolidone; The preparation method of modified coal gangue comprises the following steps: (1) crushing the coal gangue into 50-80 mesh, adding it into a phosphoric acid solution with a concentration of 8-10%, soaking it for 20-24 hours, filtering it, and drying it to obtain acid-leached coal gangue powder; (2) mixing the acid-leached gangue powder and shell powder uniformly, calcining at 800-850° C. for 1-1.5 hours under nitrogen protection, and naturally cooling to 60-80° C. after calcination to obtain calcined mixed powder; the amount of shell powder added is 15-20% of the weight of the gangue; (3) Add polyvinyl alcohol to the calcined mixed powder under vacuum at 60-80° C., stir for 1-1.5 hours, then add dimethyl silicone oil and stir for 1-1.5 hours, and then ball-mill to 120-150 mesh to obtain modified coal gangue; the amount of polyvinyl alcohol added is 20-25% of the weight of the coal gangue, and the amount of dimethyl silicone oil added is 30-35% of the weight of the coal gangue.
2. A method for constructing concrete as claimed in claim 1, characterized in that: The following steps are involved: S1, mixing 1 / 3 of the total weight of silicate cement and modified coal gangue evenly under mechanical stirring to obtain dry material; S2, adding sodium polyacrylate, micro-powder silica gel, aluminum sulfate and sodium silicate to molten sodium alginate, mixing evenly, and drying to obtain a composite admixture; S3, mixing the remaining silicate cement, fly ash, sand, gravel, air entraining agent and water evenly under mechanical stirring, then adding the composite admixture, continuing to stir and mix evenly to obtain slurry; S4, 1-1.5 hours before pouring, add the dry material obtained in S1 to the slurry obtained in S3, mix well, and obtain concrete.
Citation Information
Patent Citations
High-collapse-retentivity concrete, and preparation method and application thereof
CN103553490A
Self-compacting non-shrinkage concrete-filled steel tube
CN107572957A
Method for preparing water permeable bricks based on coal gangue
CN108383473A
Coal gangue powder used as pump concrete admixture and preparation method and application thereof
CN113264701A